Research on the mechanism of deformation and instability of surrounding rock in goaf under dynamic loading and the mechanism of active coordinated control - Xu, Kun; Chen, Yanlong; Li, Ming; Zhang, Yafei; Zhang, Pengjiao; Chen, Tian (Frontiers in Earth Science, 2025)
Dynamic loading from mining activities and surface movements can significantly affect the stability of surrounding rock in goafs, leading to large-scale deformations or even collapses of overlying strata, which may trigger extensive mining disasters and cause significant regional economic and social harm. This study focuses on the surrounding rock of a roadway near a goaf in a mining area in Shanxi. Using non-destructive testing techniques, the study analyzes the variation of bolt stress under the influence of mining activities and its impact on goaf stability. Numerical simulations were employed to investigate the deformation and stress changes of the surrounding rock under mining effects, as well as the axial force variation during the recovery process. The results show that during the mining recovery process, as the mining face advances, the axial force on the coal ribs and flexible support bolts gradually increases, while the flexible support leads to a significant stress difference between the two sides of the goaf. Under the influence of mining, the compressive stress on the roadway roof decreases, while the compressive stress on the two sidewalls increases, resulting in a large stress concentration and the formation of a low-stress pressure relief zone on the edges of the coal body. As mining-induced effects approach, the surrounding rock exhibits noticeable stress asymmetry, with the vertical stress on the flexible support side being greater than that on the coal wall side. Additionally, surrounding rock deformation gradually increases, with the lateral displacement of the two sidewalls being greater than the roof subsidence.